Perceptions of Ninth-Grade Students toward Webtoon in Vocabulary Learning at SMPN 17 Bekasi - Ardadali Aulia Putri; Agus Gunawan; Muhammad Rizky Fadhil (Universitas Galuh, 2026)
This study explored students’ perceptions of using Webtoon for learning English vocabulary and investigated how Webtoon supports vocabulary learning. A qualitative descriptive case study design was employed and eight ninth-grade students of SMPN 17 Bekasi who selected through purposive sampling were involved. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using Miles and Huberman’s (1984) model of qualitative data analysis. The findings revealed five main perceptions: (1) Webtoon is an enjoyable learning medium; (2) its visuals and storylines increase students’ interest; (3) visual context helps students understand unfamiliar vocabulary; (4) Webtoon is easier to use than traditional textbooks; and (5) visual elements support vocabulary retention. The study also identified four vocabulary learning strategies used by students: (1) guessing word meanings from context; (2) using online dictionaries and translation tools; (3) saving new vocabulary through notes and screenshots; and (4) practicing newly learned words in daily activities. Overall, the findings indicate that Webtoon can serve as an effective alternative medium for vocabulary learning by promoting vocabulary acquisition, retention, and independent learning.